PRODUKTIVITAS SAPI PERAH BERDASARKAN LAMA PEMELIHARAAN DAN TOTAL PRODUKSI SUSU PADA MASA LAKTASI - Khalidin Khalidin; Khairul Murdani; Muhammad Jakfar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The research entitled Dairy Cattle Productivity Based on Maintenance Length and Total Milk Production during the Lactation Period was conducted at the Center for Dairy Cattle and Forage Cattle Development (BPT-SP and HMT) Cikole, Lembang District, Bandung Regency, West Java Province. Analysis of research data to determine the relationship between the age group of first calving with milk production was carried out using SAS 9.1 software while descriptive analysis was calculated based on Walpole (1992). There were two variables observed, namely Age at First Marriage, Age at First Calming (FC), First and Second Lactation Milk Production. The results of the study showed that there was a significant difference in the grouping at the age of the first child or P 0.05. The calving interval did not show any significant difference or P0.05 from the first calving age group. Milk production or milk yield in the lactation period during rearing showed significant differences or P0.05.Keywords: productivity, dairy cows, lactation